Return-Volatility Interactions in the Nigerian Stock Market - OKOLI, MARGARET N (Asian Economic and Financial Review, 2012)
The study employed the GARCH (1, 1) and VAR models to ascertain the relationship between volatilities in the monetary policy variables and volatilities in the stock market returns in Nigeria between 1980 and 2010.The study showed that only exchange rate policy variable have an influence on the stock market volatility with a negative coefficient but statistically significant indicating that higher volatility in the exchange rate dampens stock market activities. This means that an increase in exchange volatility will lead to a fall in stock market volatility. Additionally, result showed that M1granger causes very significantly M2 and vice versa. Implicitly, it shows that there is “bi-directional causality” or a “bi-directional feedback” between M1 andM2.What this implies is that stabilizing interest rate will reduce the volatility in the stock market. The study also observed that there is no effect of international factor and influence on the stock market returns implying that international volatilities is not transmitted across national stock markets in Nigeria. Finally, there is the presence of volatility shocks. The study therefore suggested that government policy should focus on exchange rate to stabilize the stock market. Investors are also advised to consider the nature of volatility in exchange rate before making investment decisions.